Peningkatan Peran Pendampingan Suami pada Masa Kehamilan Istri Di Puskesmas Samata Kabupaten Gowa - Samila; Fitriani; Amina Ahmad; Nur Hidayah MS (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2025)
Pregnancy is a natural process that starts from the conception stage until the birth of the fetus, however, pregnancy can cause complications that can threaten the lives of both mother and baby. Cases of maternal mortality in the world are still very high. About 25-50% of maternal deaths are caused by problems related to pregnancy. In this case, the husband's role is the key to success. The husband's support given to his wife is a real form of the husband's concern and responsibility in the lives of his wife and children. How much does the husband know about the role of assistance in pregnancy until the birth process? The research results show that 93.3% of husbands have good knowledge, but the participation rate is only 63.3%, so there is still a need for counseling, considering the many benefits of the husband's accompanying role during the wife's pregnancy. The aim is to increase the participation and involvement of husbands in the care/care of pregnant women. Communicative information technique method and using 4 approaches, namely planning, preparation, implementation and evaluation, activities were carried out at the Smata Health Center, Gowa Regency with a total of 20 participants. The results show that the average score after counseling is better than before providing education. Average value; Good knowledge (88%), compared to before (67%), so it can be concluded that there is an increase in husbands' knowledge regarding the role of accompanying husbands during their wives' pregnancy.